Cross-sectional analysis of Indian state with highest breastfeeding initiation delays: Unveiling district level prevalence, priorities, and socio-economic correlates - Divya Sharma; Tanvi Kiran; Pritam Halder; Sujata Siwatch (Discover Social Science and Health)
Abstract Background Early initiation of breastfeeding (within the first hour postpartum) is crucial for maternal and child health, but Jharkhand exhibits the highest prevalence of delayed initiation, with over three-fourths of mothers affected. Existing literature lacks localized insights into district-level disparities and the socio-economic and healthcare determinants of delayed initiation, particularly in socio-economically disadvantaged regions like Jharkhand. Objectives This study aims to (1) assess the prevalence of delayed breastfeeding initiation across Jharkhand's districts, (2) create a spatial map categorizing districts into three priority zones (P1, P2, and P3), and (3) identify socio-economic and demographic factors associated with delayed breastfeeding initiation. Methods A cross-sectional analysis of 5,196 breastfeeding mothers from NFHS-5 (2019–2021) was conducted. District-wise prevalence rates were calculated, and a multivariable logistic regression analysis was performed using Stata-MP-17 to identify significant correlates. Results Jharkhand’s overall prevalence of delayed initiation was 77.1%, with Jamtara (86.6%) and Khunti (84.6%) reporting the highest rates. Twelve districts were categorized as Priority Level 3 (red zone). Key determinants included poor economic background (aOR = 1.379, p ≤ 0.05) and caesarean deliveries (aOR = 2.325, p < 0.001), both of which increased the odds of delayed initiation. Institutional deliveries were associated with significantly reduced odds (aOR = 0.653, p < 0.001). Conclusion High-priority districts such as Jamtara and Khunti require immediate intervention through targeted maternal health programs promoting institutional deliveries. Strategies must include tailored outreach to disadvantaged groups, awareness campaigns on breastfeeding benefits, and addressing cultural barriers, especially in rural and tribal regions, to improve maternal and child health outcomes.